PERENCANAAN PENGELOLAAN DANA PENSIUN DAN PERENCANAAN PEMBAGIAN WARISAN BERDASARKAN HUKUM ISLAM IBU SRI SUMIRAH - , Devi Erna Rachmawati ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis is a case study on asset management based on the third pillar of Wealth Management (Wealth Distribution and Transition). It discusses Planning the Pension Fund Management and planning the Islamic Law-based Inheritance Division. The client is a 55-year-old businessman in Solo-based automotive, pharmaceutical and hotel industries with the asset of IDR 64,475,000,000